Development of Interactive Electronic Modules (e-Modules) based on Flip PDF Corporate Edition on the Subject of IPA Class V Elementary School Heat Transfer Material - Caroline Monica Nirmalawaty; Harlinda Syofyan (Universitas Muhammadiyah Enrekang, 2023)
This research was conducted to answer the need for the latest electronic teaching materials, interactive and facilitating learning for teachers and grade V elementary school students, especially in the era of Revolution 4.0. The main purpose of this study is to determine the development procedures and feasibility of interactive electronic modules based on Flip PDF Corporate Edition for learning science in Class V Elementary School on Heat Transfer Material. This research is a type of Research and Development (R&D) method with the ADDIE development model. Data were collected through questionnaires, interviews, observations, and documentation. This research produces teaching materials developed with Flip PDF Corporate Edition in the form of interactive electronic modules containing text, images, audio visuals, and games.Validation by expert lecturers was carried out twice. The final result of validation by three expert lecturers (science material, media, and design) was 100%, which means that the electronic module can be used without revision. The final result of validation by language expert lecturers is 86.67% which means that the electronic module can be used with minor revisions. The results of the small group trial of the electronic module tested were 91.67%, which means that the electronic module can be used with minor revisions. The results of the field trial of the electronic module tested were 86.83%, which means that the electronic module can be used with minor revisions. The comparison of the results of the small group trial and the field trial is 88.99%, which means that the electronic module can be used with minor revisions in learning activities with the highest indicator, namely the presence of electronic modules facilitates learning for teachers and students in grade V elementary school.